Love and the Mentally Challenged: Unraveling the Affective Domain - Ranario, Roselle J. (JPAIR Multidisciplinary Research, 2011)
This study describes the affective domain specifically on the psychology of emotion among mentally challenged male students as manifested by their love and attraction towards the opposite sex. Included in the study were the Mentally Challenged pupils in selected SPED Centers, aged 15 and above who were observed to have marked attraction toward another person. Respondents and experts believed that it is risky to allow mentally challenged individuals to marry due to the following reasons: the possibility that the MC can become pregnant; she will experience trauma or psychological damage if she becomes pregnant; the likelihood that the individual will voluntarily engage in sexual activity ; be exposed to situations where sexual intercourse is imposed upon her; the inability of the MC to understand reproduction and the likely permanence of that inability of the MC to care for a child. Another presumption restricting marriages is that mentally retarded persons do not make successful marriage partners. The MC’s capacity to love starts and ends in Passionate Love. The feeling called love should be encouraged in class but with proper guidance as it helps develop the MCs socio - emotional behavior for it cultivates motivation, participation, interaction, and happiness among the mentally challenged.